60+ Full-Text Academic Theses (Ph.D. and M.A.) on Rebel Governance by Non-State Actors written in English between 2011 and 2021 - McDonald, Broderick (Perspectives on terrorism, 2021)
This bibliography contains both Ph. D. Dissertations (Ph.D.) and Master Theses (M.A.). Titles were retrieved manually by searching the Open Access Theses and Dissertations Database (OATD), using various combinations of search terms, including - but not limited to - ‘Rebel Governance’, ‘Non-State Actors’, ‘Insurgents’, ‘Terrorism’. More than 900 entries were evaluated, of which 61 were ultimately selected for this list. All theses are open source. However, readers should be aware of possible copyright restrictions. The title entries below are hyperlinked (‘clickable’), allowing access to full texts. Bibliographic entries are sorted alphabetically.